Monolayer Graphene/Germanium Schottky Junction As High-Performance Self-Driven Infrared Light Photodetector - Zeng, Long-Hui; Wang, Ming-Zheng; Hu, Han; Nie, Biao; Yu, Yong-Qiang; Wu, Chun-Yan; Wang, Li; Hu, Ji-Gang; Xie, Chao; Liang, Feng-Xia; Luo, Lin-Bao (ACS applied materials & interfaces, 2013)
We report on the simple fabrication of monolayer graphene (MLG)/germanium (Ge) heterojunction for infrared (IR) light sensing. It is found that the as-fabricated Schottky junction detector exhibits obvious photovoltaic characteristics, and is sensitive to IR light with high I light/I dark ratio of 2 × 104 at zero bias voltage. The responsivity and detectivity are as high as 51.8 mA W–1 and 1.38 × 1010 cm Hz1/2 W–1, respectively. Further photoresponse study reveals that the photovoltaic IR detector displays excellent spectral selectivity with peak sensitivity at 1400 nm, and a fast light response speed of microsecond rise/fall time with good reproducibility and long-term stability. The generality of the above results suggests that the present MLG/Ge IR photodetector would have great potential for future optoelectronic device applications.